SOME QUESTIONS ABOUT THE ECOLOGICAL CONDITIONS OF GROWING AGRICULTURAL PLANTS IN THE SOUTHERN ARAL SEA REGION - Tleumuratova Bibigul Sarybaevna; Kublanov Jalgasbay Jumabaevich; Dauletbayeva Guliya Yelmuratovna; Urumbaev Azamat Ernazarovich; Sultashev Renat Genjebaevich (Web of Journals Publishing, 2025)
This review article analyzes and discusses potential links between environmental conditions in the Southern Aral Sea region and the food safety of plant products. A significant place in the article is devoted to the dynamics of diseases associated with the deterioration of environmental conditions (climatic changes, pollution of soils, water and atmosphere, soil salinization). A literary review of foreign publications has shown that chemical pollution of the environment is considered to be the dominant risk factor for food safety. For the UP region, an additional environmental factor is the drying up of the Aral Sea, which is inextricably linked to the removal of salts from the drained bottom, which contain toxic sulfates. An important factor in food safety risks is climate warming, which provokes an increase in plant pathogens and parasites, as well as shortening the transportation and storage time of agricultural products.